JACOBSON'S PROGRESSIVE MUSCLE RELAXATION (JPMR) TRAINING TO REDUCE ANXIETY AND DEPRESSION AMONG PEOPLE LIVING WITH HIV - Bommareddi, Prameelarani; Valsaraj, Blessy Prabha; Shalini (Journal of Health and Allied Sciences NU, 2014)
Background: The term AIDS refers only to the last stage of the HIV infection. AIDS can be called as our modern pandemic affecting both industrialized and developing countries.Objectives: To assess the anxiety and depression among people living with HIV as measured by HADS (Hospital Anxiety and Depression Scale), to determine the effectiveness of JPMR in terms of reduction in the mean posttest anxiety and depression scores, to find the association of anxiety and depression among people living with HIV with selected demographic and disease specific variables.Materials and Methods: one group pre test and post test design was used. 30 people living with HIV who were admitted at ART center, District Hospital, Udupi were selected and different scales on anxiety and depression scale for people living with HIV were administered. Purposive sampling technique was used for the study.Results: Out of 30 subjects, 13.30% (4) experienced abnormal anxiety and 16.7% (5) abnormal depression. There was significance difference between mean difference of pretest and post test scores of anxiety (t=8.471, df=29, p=0.001) and depression (t=6.811, df=29, p=0.001). Anxiety is independent of the selected variables (Demographic and disease specific). Depression is dependent on previous history of psychiatric illness (÷2=6.584, df =2, p=0.037).Conclusion: JPMR is a simple non-invasive, cost effective method. The result showed that JPMR training had a positive effect in reducing the anxiety and depression and JPMR can be used as an effective alternative therapy.
Keywords: Anxiety; Depression; JPMR and People living with HIV